Advances in Quantum Field Theory - Ketov, Sergey (IntechOpen, 2012)
Quantum Field Theory is now well recognized as a powerful tool not only in Particle Physics but also in Nuclear Physics, Condensed Matter Physics, Solid State Physics and even in Mathematics. In this book some current applications of Quantum Field Theory to those areas of modern physics and mathematics are collected, in order to offer a deeper understanding of known facts and unsolved problems.